Hitching-in (1914)
A photograph from a dismantled album of World War One-related photographs in the William Okell Holden Dodds fonds. Brigadier General Dodds joined the Canadian Expeditionary Force in 1914 and was commanding officer of the 5th Canadian Division Artillery and served in France from 1917-1918. Photos in the album were taken in France and Germany with many "official photographs" taken during the war and probably just afterward.